2021
DOI: 10.1093/eurjpc/zwab120
|View full text |Cite
|
Sign up to set email alerts
|

Incremental prognostic value of non-alcoholic fatty liver disease over coronary computed tomography angiography findings in patients with suspected coronary artery disease

Abstract: Aims This study aimed to investigate additional risk stratification benefits of hepatic steatosis (HS) concurrently assessed during coronary computed tomography angiography (CTA) in a large patient cohort with suspected stable coronary artery disease (CAD). Methods and results In this prospective study, 1148 Japanese outpatients without a history of CAD who underwent coronary CTA for suspected stable CAD (mean age 64 ± 14 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…The current study population was derived from a prospective, single centre, cohort study comprising Japanese patients who underwent coronary CTA at Okayama University. A study including some patients in this cohort has already been published [ 12 ]. We prospectively gathered data on the clinical features, coronary CTA findings, and patient outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The current study population was derived from a prospective, single centre, cohort study comprising Japanese patients who underwent coronary CTA at Okayama University. A study including some patients in this cohort has already been published [ 12 ]. We prospectively gathered data on the clinical features, coronary CTA findings, and patient outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Coronary CTA images were obtained using a De nition Flash scanner (Siemens Medical Solutions, Erlangen, Germany) as previously described [4]. On coronary CTA analysis, we evaluated coronary artery segments with a diameter of >2 mm and de ned plaque characteristics in accordance with the Society of Cardiovascular Computed Tomography [14].…”
Section: Coronary Cta Analysesmentioning
confidence: 99%
“…This study was a post-hoc analysis of PCAT attenuation from a prospective cohort study that evaluated the impact of hepatic steatosis on coronary artery disease and its prognosis. The principal study design has been described previously [4]. Brie y, patients who underwent coronary CTA for suspected stable coronary artery disease at Okayama University between August 2011 and December 2016 were enrolled in this cohort study.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…While NAFLD primarily affects liver structure and function, leading to morbidity and mortality from liver failure, cardiovascular diseases (CVDs) are the most common cause of death in patients with early NAFLD [ 2 ]. Moreover, emerging evidence has demonstrated that NAFLD is a risk factor for developing atherosclerotic cardiovascular complications, such as stroke and myocardial infarction [ 3 , 4 , 5 ]. We previously reported a significant association between NAFLD and the presence of high-risk plaques (HRP) on coronary computed tomography angiography (CCTA), which increased the likelihood of cardiovascular events [ 6 ].…”
Section: Introductionmentioning
confidence: 99%